‘Lessons learned’ from trialists who adapted a complex intervention for remote delivery within a trial as a result of the COVID-19 pandemic: a scoping review - Howes, Ella; Smith, Samuel G.; Gillies, Katie; Zhang, Lisa; Farrin, Amanda J. (Current controlled trials in cardiovascular medicine, 2025)
Background During the COVID-19 pandemic, complex interventions being evaluated in randomised controlled trials were often rapidly adapted from in-person to remote delivery. Such adaptations to intervention delivery have the potential to cause unintended consequences and affect important aspects of trial generalisability and interpretation. This scoping review aimed to identify the ‘lessons learned’ from trialists who adapted and remotely delivered a complex intervention within a trial because of the COVID-19 pandemic. Gaining a better understanding of trialists’ experiences of adapting interventions for remote delivery will identify where more in-depth investigation and guidance is needed. Methods The Joanna Briggs Institute (JBI) scoping review guidelines were followed. The search was developed for MEDLINE and adapted for Web of Science, PsycINFO, EMBASE, and Cochrane. Data were extracted on study characteristics, methods reported to adapt interventions, and the challenges and facilitators of the process of adaptation and remote intervention delivery. Data on remote intervention delivery were organised using the upper level of the Behaviour Change Intervention Ontology. Results Fifteen articles were eligible for inclusion describing insights from 16 randomised controlled trials, across a range of populations and trial designs. Most discussion focused on challenges and facilitators of the remote delivery of the complex intervention. These included privacy and safety concerns of intervention delivery within the home setting, and technological issues of remote delivery via video call. The most frequently reported facilitator was the use of an environmental inventory before intervention delivery to check the space in which participants were located, and the materials available to them. Conclusion Suitability of an intervention for remote delivery depends not only on whether it is originally delivered via a digital technology, but also the extent to which it requires human facilitation and support. Privacy and safety concerns in the home environment could impact trial participation in a remotely delivered intervention. Further research is needed to explore how trialists can effectively prepare for and manage the challenges of remote intervention delivery. Guidance developed to support adaptation of an intervention for remote delivery within a trial should be specific to the mode of delivery used.